2017
DOI: 10.1002/hep.29406
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant covalently closed circular DNA of hepatitis B virus induces long‐term viral persistence with chronic hepatitis in a mouse model

Abstract: rcccDNA was intrinsically stable in vivo, enabling long-term persistence in the context of chronic hepatitis, and viral persistence, in turn, may promote progression of chronic liver disease; our study also presented a surrogate model of HBV cccDNA persistence in mice that could advance our understanding of the pathogenesis of chronic hepatitis B. (Hepatology 2018;67:56-70).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 37 publications
(58 reference statements)
2
83
0
2
Order By: Relevance
“…To investigate the potential sensor for HBV cccDNA, we established a recombinant cccDNA (rcccDNA) cell model by transfecting prcccDNA plus pCMV‐Cre (prcccDNA/Cre) into Huh7 cells as described . This model is credited with producing high levels of rcccDNA in the hepatic nuclei, which has been proven to be a surrogate for the natural cccDNA minichromosome . As PRRs often possess two properties (physical interaction with DNA and being transcriptionally inducible by cytokines as part of a positive feedback loop to sustain innate immune responses), we treated this rcccDNA cell model with or without IFN‐α and then tested the possible sensors for cccDNA by ChIP assays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the potential sensor for HBV cccDNA, we established a recombinant cccDNA (rcccDNA) cell model by transfecting prcccDNA plus pCMV‐Cre (prcccDNA/Cre) into Huh7 cells as described . This model is credited with producing high levels of rcccDNA in the hepatic nuclei, which has been proven to be a surrogate for the natural cccDNA minichromosome . As PRRs often possess two properties (physical interaction with DNA and being transcriptionally inducible by cytokines as part of a positive feedback loop to sustain innate immune responses), we treated this rcccDNA cell model with or without IFN‐α and then tested the possible sensors for cccDNA by ChIP assays.…”
Section: Resultsmentioning
confidence: 99%
“…Precursor plasmid rcccDNA (prcccDNA) and Crerecombinase expression plasmid (pCMV-Cre) were cotransfected into Huh7 cells to produce recombinant cccDNA (rcccDNA) as reported by Qi et al (15) Nuclear rcccDNA has been demonstrated to be epigenetically organized as a minichromosome and can be used as a cccDNA surrogate for HBV studies. (15)(16)(17) To investigate the effect of IFI16 overexpression on cccDNA, prcccDNA/pCMV-Cre together with FLAGtagged plasmid IFI16 (pIFI16-FLAG; Addgene, #35064) was transfected into Huh7 cells using lipofectamine 2000 (Invitrogen, Carlsbad, CA). Small interfering RNA (siRNA) specific for IFI16 (sense: 5′-UGCUGAACGCAACAGAAUCAU-3′ and antisense: 5′-AUGAUUCUGUUGCGUUCAGCA-3′) or control siRNA was transfected into Huh7 cells by HiPerFect Transfection Reagent (Qiagen, Hilden, Germany).…”
Section: Plasmid or Small Interfering Rna Transfection And Hbv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tet-Off and Tet-On gene expression systems were from Clontech (Mountain View, USA). prcccDNA and pCMV-Cre plasmids were constructed previously [20,21]. prcccDNA contains a precursor of recombinant HBV cccDNA which can be formed by Cre-mediated recombination in cells and mice.…”
Section: Plasmids and Lentivirusesmentioning
confidence: 99%
“…S12i (online), no obvious binding of SAMHD1 to HBV DNA was detected. For in vivo study, a mouse model of HBV cccDNA was employed [20,21]. In such a system, a recombinant cccDNA (rcccDNA) precursor plasmid (prcccDNA) and pCMV-Cre were hydrodynamically injected through tail vein to transfect mouse liver.…”
Section: Samhd1 and Irf1 Restrict The Expression Of Exogenous Dna Andmentioning
confidence: 99%